Gd3 Triangles in a Polyoxometalate Matrix: Tuning Molecular Magnetocaloric Effects in Gd30M8 Polyoxometalate/Cluster Hybrids Through Variation of M2+. Issue 10 (13th October 2021) - Ibrahim, Masooma; Peng, Yan; Moreno-Pineda, Eufemio; Anson, Christopher E.; Schnack, Jürgen; Powell, Annie K.
Abstract : Magnetocaloric Effects A family of nanoscale heterometallic 3d‐Gd III compounds ligated by lacunary polyoxometalates (POMs) and featuring weakly antiferromagnetically coupled Gd III 3 triangles dispersed within the diamagnetic POM matrix allows tuning of the magnetocaloric effect by variation of the 3d‐cation. This provides a route for the development of low‐temperature, energy‐efficient and environmentally friendly sub‐Kelvin magnetic cooling technologies. More details can be found in article number 2100052 by Masooma Ibrahim, Jürgen Schnack, Annie K. Powell, and co‐workers.